Effects of partial replacement of soybean meal with Chlorella vulgaris and lysozyme on diarrheal incidence, plasma biochemical parameters, and immunity of weaned piglets - Azad, Md. Abul Kalam; Li, Bowen; Ye, Ting; Qin, Binghua; Zhu, Qian; Martinez, Yordan; Kong, Xiangfeng (Frontiers in Veterinary Science, 2025)
IntroductionThe study aimed to investigate the effects of Chlorella vulgaris and lysozyme on growth performance, diarrhea rate, immune function, plasma biochemical parameters, and gut microbiota and metabolites of weaned piglets.MethodsThirty weaned Xiangcun black piglets (BW, 11.47 ± 1.13 kg) were randomly assigned to one of three treatment groups: corn-soybean meal-based basal diet (CON group), soybean meal replaced with 5% C. vulgaris (CHV group), and soybean meal replaced with 5% C. vulgaris and 100 mg/kg lysozyme (LYSO group).ResultsGrowth performance was not affected by C. vulgaris or C. vulgaris with lysozyme supplementation, while soybean meal partially replaced by C. vulgaris without lysozyme reduced the diarrhea rate of weaned piglets. Plasma biochemical analysis showed that plasma albumin, alkaline phosphatase, and high-density lipoprotein-cholesterol (HDL-C) levels in the CHV group and the total cholesterol and HDL-C levels in the LYSO group were higher when compared with the CON group. The LYSO group had increased interleukin (IL)-10 level in the jejunum and IL-1β level in the ileum while having a decreasing IL-6 level in the jejunum of piglets. Additionally, although Firmicutes and Megashaera_A abundances and short-chain fatty acid concentrations (including acetate, propionate, butyrate, and valerate) were reduced in the CHV group, but several beneficial bacteria (such as Actinobacteroita, Faecealibacterium, and Anaerovibrio) abundances were increased in the LYSO group.DiscussionIn summary, dietary C. vulgaris or C. vulgaris with lysozyme supplementation improved health of piglets in some contexts without affecting growth performance. Therefore, soybean meal replaced by 5% C. vulgaris with or without lysozyme as sustainable feed ingredients in piglet diets could be a viable alternative approach.